2020
DOI: 10.1111/ddi.13078
|View full text |Cite
|
Sign up to set email alerts
|

Combining US and Canadian forest inventories to assess habitat suitability and migration potential of 25 tree species under climate change

Abstract: AimTo evaluate current and future dynamics of 25 tree species spanning United States and Canada.LocationUnited States and Canada.MethodsWe combine, for the first time, the species compositions from relative importance derived from the USA’s Forest Inventory Analysis (FIA) with gridded estimates based on Canada's National Forest Inventory (NFI‐kNN))‐based photo plot data to evaluate future habitats and colonization potentials for 25 tree species. Using 21 climatic variables under RCP 4.5 and RCP 8.5, we model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 81 publications
0
32
0
Order By: Relevance
“…Lack of propagules of warm-adapted species within most of the boreal range impeded potential AGB recovery from boreal conifer decline. In fact, thermophilous species migration towards more northern, suitable conditions will be strongly outpaced by the northward shift of the isotherms even under moderate forcing (Brice et al 2019; Prasad et al 2020). Considering their limited dispersal abilities, we projected that thermophilous species would colonize sites only few tens of km north of their actual northern range (Suppl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of propagules of warm-adapted species within most of the boreal range impeded potential AGB recovery from boreal conifer decline. In fact, thermophilous species migration towards more northern, suitable conditions will be strongly outpaced by the northward shift of the isotherms even under moderate forcing (Brice et al 2019; Prasad et al 2020). Considering their limited dispersal abilities, we projected that thermophilous species would colonize sites only few tens of km north of their actual northern range (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Mat S2), compromising their potential expansion within the boreal forest. Notwithstanding the increased disturbance rates, thermophilous species are therefore less likely to extensively compensate AGB losses by boreal species by introducing a significant “migration lag” within the boreal forest (Taylor et al 2017; Prasad et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, certain tree species that currently act as major allergen sources like birch may dwindle or disappear in some areas as their range contracts northward, although they may also expand their distribution into areas of higher elevation (Dyderski et al, 2018). Such displacements do not happen straight away, however, as there is a lag due to species plasticity favouring population persistence and dispersion capability as well as species competence limiting migration rates (Prasad et al, 2020). Although, it has been suggested that, due to intraspecific variations, warm margin populations are the most vulnerable to climate change (Fréjaville et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While assisted migration has received significant attention as a climate change adaptation strategy [88,89], diversification of forestry practices (e.g., use of alternative silviculture systems, planting more tree species, prioritizing harvest in areas of high risk of distur-bance) and genetic diversification in particular have also been proposed to buffer some of the uncertainty in climate change projections [1,31,90]. Crop diversification is commonly practiced by farmers to mitigate uncertainty associated with crop prices and variability in production due to pest outbreaks and extreme weather [91], and portfolio diversification is widely used by investors to stabilize returns from fluctuating markets [92].…”
Section: Tackling Uncertainty By Promoting Genetic Diversificationmentioning
confidence: 99%